Intranasal Vaccination with Mannosylated Chitosan Formulated DNA Vaccine Enables Robust IgA and Cellular Response Induction in the Lungs of Mice and Improves Protection against Pulmonary Mycobacterial Challenge - Wu, Manli; Zhao, Haoxin; Li, Min; Yue, Yan; Xiong, Sidong; Xu, Wei (Frontiers in Cellular and Infection Microbiology, 2017)
Induction of specific humoral and cellular immunity in the lung airways is proposed to be critical for vaccine protection against Mycobacterium tuberculosis (M. tb). To facilitate airway delivery and antigen targeting to the antigen presenting cells in the alveoli, we employed mannosylated chitosan (MCS) to formulate a multi-T-epitope DNA vaccine, pPES, as an intranasal TB vaccine. MCS -DNA nanoparticles appeared spherical with the average particle sizes as 400 nm. HSP65-specific bronchoalveolar lavage fluid SIgA level was significantly elevated by 4 doses of MCS-pPES intranasal immunization as compared to chitosan (CS)-DNA and BCG vaccine. I.n. immunization with MCS-DNA induced a modest peptide-specific Th1(IFN-γ, TNF-a and IL-2) response in the spleen, while a potent poly-functional CD4+ T response that largely produced TNF-α and IFN-γ, as well as IL-2 in the lung, qualitatively better than that induced by CS-DNA and BCG vaccination. Such response by i.n. immunization with MCS-DNA provided improved protection in the lung against airway Mycobacterial bovis BCG challenge over i.n. CS-DNA and DNA, that is comparable to protection achieved by s.c. BCG vaccination. This enhanced protection was correlated with much greater accessibility of DNA particles to the alveolar macrophages in the lung mediated by man-chitosan. Thus, man-chitosan TB vaccine represents a promising vaccine platform capable of eliciting robust multi-functional T response in the lung mucus and achieving enhanced mucosal immune protection against pulmonary TB.